2020
DOI: 10.26444/jpccr/118949
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic suceptibility of<i> Escherichia coli</i> isolated in cases of urinary tract infection in Nsukka, Nigeria

Abstract: Introduction and objective. The study was carried out to determine the occurrence and antibiotics susceptibility profile of Escherichia coli recovered from patients with urinary tract infection (UTI) in Nsukka, southeastern Nigeria. Materials and method. Midstream urine samples were obtained from 266 outpatients. Standardized questionnaires were used to collect relevant information from the subjects. Urine samples were plated on MacConkey and eosin methylene blue agar. E. coli isolates were identified using st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…[33] The findings of the current study demonstrated that ceftazidime exhibited 100% resistance against gram-negative bacteria. This resistance rate aligns with previous studies conducted in Nigeria (100%) [35] and Ethiopia, specifically Gondar (100%). [36] Additionally, E coli displayed resistance to ampicillin in the present study, which is consistent with previous reports from Ethiopia (80%-100%) [3] and Saudi Arabia (89%).…”
Section: Discussionsupporting
confidence: 92%
“…[33] The findings of the current study demonstrated that ceftazidime exhibited 100% resistance against gram-negative bacteria. This resistance rate aligns with previous studies conducted in Nigeria (100%) [35] and Ethiopia, specifically Gondar (100%). [36] Additionally, E coli displayed resistance to ampicillin in the present study, which is consistent with previous reports from Ethiopia (80%-100%) [3] and Saudi Arabia (89%).…”
Section: Discussionsupporting
confidence: 92%